Pengaruh Kepemimpinan Visioner Kepala Sekolah dan Komitmen Organisasi Terhadap Produktivitas Kerja Guru MIPA Di SMAN Se- Kabupaten Dharmasyraya - Rinny S; Marjoni Imamora; Demina Demina; Fadriati Fadriati; Isra Nurmai Yenti (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Teacher productivity is a key factor in improving the quality of secondary education. However, various challenges such as low instructional innovation, administrative delays, and limited professional engagement remain prevalent among science teachers. This study aims to analyze the influence of visionary leadership of school principals and organizational commitment on the productivity of science teachers in public senior high schools in Dharmasraya Regency. This research employed a quantitative approach with a correlational design. The population consisted of 104 science teachers from 16 public senior high schools, with a sample of 83 teachers selected using cluster random sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included descriptive statistics and multiple linear regression using SPSS. The results indicate that visionary leadership has a positive but not statistically significant effect on teacher productivity (p > 0.05). In contrast, organizational commitment has a positive and significant effect (p < 0.05). Simultaneously, both variables significantly influence teacher productivity with a coefficient of determination of 56.1%. These findings highlight that organizational commitment is the most dominant factor influencing teacher productivity.